The evolution of Ghanaian Internet cafés, 2003–2014. Issue 1 (2nd January 2017) - LeBlanc, Matthew; Shrum, Wesley
ABSTRACT: Two main perspectives characterize current research on Internet cafés in the developing world. The "inclusionary" perspective represents these public digital spaces as the most important source of connectivity and inclusion for the global population. The "transitional" perspective represents Internet cafés as a dying business whose obituary is long overdue. This study describes a search for two dozen Internet cafés in Ghana, based on establishments first identified in 2003, accompanied by interviews with patrons and café attendants. Our initial exploration supported the transitional prediction that cafés would be shuttered or replaced by traditional businesses. However, an expanded search led us to the conclusion that "walking distance" replacements for all cafés remained available, supporting the inclusionary view. Qualitative interviews revealed the shift of cybers to business services and their continued importance as online spaces for disadvantaged populations.